Professional development of teachers in the conditions of a non-state educational institution - Olga Alexandrovna Rogozhina (Вестник Майкопского государственного технологического университета, 2023)
The article reveals the relevance of professional development of teachers of a non-governmental educational institution, due to the innovative nature of their activities and focus on revealing the potential of each child and the formation of his/her personality. The research problem has been initiated by increasing the role of professional communities as a form of advanced training for teachers and their opportunities for teachers of non-governmental educational institutions. The purpose of the study has been to justify theoretically, develop and test experimentally the effectiveness of a professional community model of teachers of a non-governmental educational institution as a self-learning organization. A number of theoretical and experimental methods have been used in the research, which included analysis of literature, modeling, design, data generalization, survey, observation, questionnaire, experiment, methods of mathematical and statistical data processing. In course of the research the following characteristics of activities of non-governmental educational institutions have been identified: a synergistic approach to administration; administration optimality; a non-governmental educational institution’s concept and development strategy and orientation to social needs. The main ideas for designing professional development of teachers of a non-governmental educational institution are as follows: interconnection of professional development with the concept of a non-governmental educational institution; consistency of professional development programs with the goals and values of school; orientation of professional development to improve the quality of education; providing professional development with evidence and examination of the effectiveness of educational activities; use of cooperation and expert task; duration of professional development programs and the priority of professional development in the activities of school management.